Caracterização dos resíduos do processamento de mandioca para produção de bioetanol - Camacho, Ileana Andrea Ordoñez [UNESP]; Cabello, Claudio [UNESP] (EIA Energy in Agriculture, 2012)
Aiming to get the best economic advantage in ethanol production from cassava roots, this study presented a physiochemical characterization from two different types of solid waste in two types of processing of the raw materials in manufacturing ethanol. The processing of cassava roots begins with the disintegration and washing the roots with the addition of 20% more water to obtain a pulp which was treated and stirred in the reactor while adding enzyme α-amylase at a temperature of 90°C for 2 hours. Then we performed a pH adjustment while lowering the temperature to 60 ° C with the addition of the enzyme amiloglucosidase and then stirring for 14 hours. The hydrolyzate obtained was the source of two types of waste which are: i) Solid residue obtained after filtration of the hydrolyatze and ii) Solid waste obtained from filtering wine after alcoholic fermentation of the hydrolyzate with the addition of a dried yeast strain Y-940 manufactured by MAURI OF BRAZIL SA (2%) at a temperature of 25º C. The results of the laboratory analysis showed that the byproducts derived from the hydrolysis and fermentation showed very similar chemical compositions. With levels between 39 and 41% fiber, 0.5% lipids, 20 and 30% carbohydrates, protein 0.5 and 1.50, 6 and 8% acidity, and 20 and 30% soluble solids.

A fim de se obter um melhor rendimento econômico na produção de etanol, a partir das raízes de mandioca, o presente trabalho realizou a caracterização físico-química de resíduos sólidos gerados em dois tipos diferentes de processamento da matéria prima numa planta de fabricação de etanol. O processamento das raízes de mandioca teve inicio com a lavagem e desintegração das raízes com adição de 20% de água até obter uma polpa que foi tratada em reator agitado adicionando enzima α-amilase e temperatura de 90°C por 2 horas. Em seguida, realizou-se o ajuste de pH a 4,5, abaixamento da temperatura para 60°C e adição de enzima amiloglucosidase com agitação por 14 horas. O hidrolisado obtido foi a fonte dos dois tipos de resíduo quais sejam: i) resíduo obtido da filtração do hidrolisado e; ii) resíduo obtido da filtração do vinho alcoólico após fermentação do hidrolisado com adição de levedura desidratada da cepa Y-940 fabricada pela MAURI DO BRASIL S.A (2%) e temperatura ambiente (25ºC). Os resultados das analises laboratoriais mostraram que os subprodutos resultantes da hidrolise e da fermentação apresentaram composição química muito semelhante. Com teores entre 39 e 41% de fibra, 0,5% de lipídeos, 20 e 30% de carboidratos, 0,5 e 1,50 de proteína, 6 e 8 % de acidez e, 20 e 30% de sólidos solúveis.
Characterization of wastes in cassava prodution for use as bioethanol
Keywords: Ethanol; Cassava; Waste; Composition; Etanol; Mandioca; Composição